2019
DOI: 10.1111/jdv.15525
|View full text |Cite
|
Sign up to set email alerts
|

Primary prevention of keratinocyte carcinoma among outdoor workers, the general population and medical professionals: a systematic review updated for 2019

Abstract: Worldwide 2–3 million cases of keratinocyte carcinoma (KC) are diagnosed annually. Sun‐related knowledge is essential for adequate protection against solar ultraviolet radiation (UVR), the main risk factor for KC. The goal was (i) to provide an updated overview of primary prevention against KC including skin cancer‐related knowledge, attitudes and sun protection behaviour (SPB) of outdoor workers, the general population and medical professionals as well as (ii) to evaluate the effectiveness and acceptability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 110 publications
(516 reference statements)
3
22
0
4
Order By: Relevance
“…The findings of this study in a population with predominance of dark skin color are consistent with the general trend of lack of awareness about proper use of sunscreen in other populations . The findings of this study indicate a clear difference in the use of sunscreens between males and females.…”
Section: Discussionsupporting
confidence: 88%
“…The findings of this study in a population with predominance of dark skin color are consistent with the general trend of lack of awareness about proper use of sunscreen in other populations . The findings of this study indicate a clear difference in the use of sunscreens between males and females.…”
Section: Discussionsupporting
confidence: 88%
“…Obwohl aktuelle Studien für Deutschland einerseits auf ein geringeres Hautkrebsrisiko andererseits auf eine spätere Diagnosestellung sowie Behandlung von Hautkrebs für die ländliche Bevölkerung verglichen mit der Stadtbevölkerung hinweisen [3,17], liegen bisher kaum Daten zur Inanspruchnahme von Sonnenschutzmaßnahmen in der ländlichen Bevölkerung Deutschlands vor. Basierend auf Untersuchungsergebnissen anderer Länder [7,13] und verschiedener Außenberufsgruppen in Deutschland, die überwiegend im ländlichen Raum tätig sind [25,28,30], lässt sich jedoch eine geringe Anwendung von Sonnenschutzmaßnahmen in der deutschen Landbevölkerung ableiten.…”
Section: Hintergrund Und Fragestellungunclassified
“…(Supplementary Table 3) Despite overwhelming scrutiny, the UVI has been adopted by many governments as the standard platform for public communication of UV exposure risk since its inception by the WHO 1994 [37]. Many of the research efforts detailing UVI knowledge have shown there is a minimal understanding of the UVI by the public [51,54,[85][86][87][88][89][90] and that lower UVI value recommendations underpredict erythemal risk [91][92][93]. Medical professionals have similarly displayed limited knowledge or use of the UVI [94][95][96].…”
Section: Resultsmentioning
confidence: 99%